Pleural mesothelioma: is the surgeon still there?. (14th June 2018) - Opitz, I; Weder, W
Abstract: Malignant pleural mesothelioma (MPM) is a rare malignancy with some unique characteristics. Tumor biology is aggressive and prognosis is poor. Despite more knowledge on histology, tumor biology and staging, there is still a relevant discrepancy between clinical and pathologic staging resulting in difficult prediction of prognosis and treatment outcome, making treatment allocation more challenging than in most other malignancies. After years of nihilism in the late 80s, a period of activism started evaluating different treatment protocols combined with research driven mainly by academic centers; at the time, selection was based on histology and stage only. This period was important to gain knowledge about the disease. However, the interpretation of data was difficult since selection criteria and definitions varied substantially. Not surprisingly, until now there is no common agreement on best treatment even among specialists. Hence, a review of our current concepts is indicated and personalized treatment should become applicable in the future. Surgery was and still is an issue of debate. In principle, surgery is an effective approach as it allows macroscopic complete elimination of a tumor, which is relatively resistant to medical treatment. It helps to set the clock back and other therapies that have also just a limited effect can be applied sequentially before or after surgery. Furthermore, to date best long-term outcome is reported from surgical series in combination with other modalities. However, part of the community considers surgery associated with too high morbidity and mortality when balanced to the limited life expectancy. This criticism is understandable, since poor results after surgery are reported. The present article will review the indication for surgery and discuss the different procedures available for macroscopic complete resection—such as lung-preserving (extended) pleurectomy/decortication as well as extrapleural pneumonectomy to illustrate that 'The surgeon is still there!'